Low Power 24 GHz ad hoc Networking System Based on TDOA for Indoor Localization - Jung, Melanie; Fischer, Georg; Weigel, Robert; Ußmüller, Thomas (ISPRS International Journal of Geo-Information, 2013)
This paper introduces the key elements of a novel low-power, high precision localization system based on Time-Difference-of-Arrival (TDOA) distance measurements. The combination of multiple localizable sensor nodes, leads to an ad hoc network. Besides the localization functionality this ad hoc network has the additional advantage of a communication interface. Due to this a flexible positioning of the master station for information collection and the detection of static and mobile nodes is possible. These sensor nodes work in the 24 GHz ISM (Industrial Scientific and Medical) frequency range and address several use cases and are able to improve various processes for production scheduling, logistics, quality management, medical applications and collection of geo information. The whole system design is explained briefly. Its core component is the frequency modulated continuous wave (FMCW) synthesizer suitable for high performance indoor localization. This research work focuses on power and size reduction of this crucial system component. The comparison of the first and second generation of the system shows a significant size and power reduction as well as an increased precision.
elib2cris::1512001600,jung2013
Keywords: fmcw; tdoa; ad hoc networking; pll; synthesizer; tspc; frequency divider